PENYUSUNAN DAN EVALUASI HACCP PROSES PRODUKSI NATA DE COCO DI CV. AGRINDO SUPRAFOOD - , SATRIA INDRA DHARMA, Dr. Ir. Wahyu Supartono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
CV. Agrindo Suprafood is a company that produces the product nata de coco coconut water-based. The process of making nata de coco include coconut water filtration, boiling, cooling, fermentation, harvest, husk pembesetan nata, splitting, cutting, sorting, draining, and packaging process. In the process of making nata de coco, CV. Agrindo Suprafood always put product quality nata de coco nata de coco to damage during the process so as to produce products of good quality and safe for consumption. It requires industrial nata de coco CV. Agrindo Suprafood to undertake prevention efforts by conducting food safety assurance system is tight. In this thesis aims to determine the hazards that occur in the production process of nata de coco by using the HACCP system is a quality management system to effectively and efficiently ensure food security. HACCP systems analysis and careful control of the hazard or risk of biological, chemical, and physical of raw materials, production processes, handling the manufacturing, distribution and consumption of the final product. From the observation that there is, that the location of the critical control points in the production process of nata de coco contained in the fermentation process, draining and packing, because prevention is implemented can not reduce the dangers that arise.